Correlates of soft drink and fruit juice consumption among Swedish adolescents - Vågstrand, Karin (2008)
The aim of the study was to investigate how soft drink and fruit juice consumption in teenagers is associated with life-style, other food choices, eating behaviour and maternal characteristics. A cross-sectional study of 16-year-old girls (n 275) and boys (n 199) and their mothers was undertaken. Questionnaires were used to assess habitual dietary intake, eating behaviour, physical activity, smoking and educational level. Weight and height were measured. It was found that eating breakfast less than five times per week was independently associated with a high soft drink consumption in both girls and boys. A low intake of cooked meals and milk and a high intake of salty snacks were associated with soft drinks in boys only, and a low intake of fruits in girls only. A high maternal juice intake, low milk and high fruit consumption were independent correlates of fruit juice intake in both girls and boys. In girls, being a smoker, having a smoking mother, a high soft drink intake, scoring low on emotional eating and high on cognitive restraint were also associated with fruit juice intake. A low intake of soft drinks and cooked meals was associated with fruit juice intake in boys only. Neither soft drinks nor fruit juice was associated with BMI. In conclusion, a high intake of both fruit juice and soft drinks were associated with a lower intake of foods such as milk and cooked meals. It might be possible to influence fruit juice intake among teenagers by aiming at their mothers, whereas the adolescents themselves should be targeted when the aim is to reduce soft drink consumption.